2008
DOI: 10.1017/s1479262108923807
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid content in different legume germplasm seeds quantified by HPLC

Abstract: Flavonoid content was quantified by high performance liquid chromatography (HPLC) and seed-coat colour was recorded from different legume seeds. Soybean seeds generally contained significantly higher amounts of daidzein (315 -354 mg/g), genistein (438 -458 mg/g), kaempferol (38 -68 mg/g) and total measured flavonoids (892 -917 mg/g), while cowpea and peanut seeds contained a significantly higher amount of quercetin (214 -280 mg/g and 133-289 mg/g, respectively) than the other legumes tested. Significant variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 15 publications
3
54
1
Order By: Relevance
“…In comparison, chlorhexidine 0.02% (drug control) showed inhibitory effect on the growth of A. castellanii cysts by 55.3-80.2% in all incubation periods. The obtained cysticidal effect of A. hypogaea L. in this study may be attributed to quercetin, plantderived flavonoids which represent a major component responsible for its biological actions (Wang et al 2008). It has been reported that quercetin had inhibited DNA synthesis and arrested cell cycle progression in Leishmania donovani promastigotes, leading to apoptosis (Koide et al 2002).…”
Section: Discussionmentioning
confidence: 61%
“…In comparison, chlorhexidine 0.02% (drug control) showed inhibitory effect on the growth of A. castellanii cysts by 55.3-80.2% in all incubation periods. The obtained cysticidal effect of A. hypogaea L. in this study may be attributed to quercetin, plantderived flavonoids which represent a major component responsible for its biological actions (Wang et al 2008). It has been reported that quercetin had inhibited DNA synthesis and arrested cell cycle progression in Leishmania donovani promastigotes, leading to apoptosis (Koide et al 2002).…”
Section: Discussionmentioning
confidence: 61%
“…Flavonols, isoflavonols and isoflavones are the major among the total flavonoids in peanut kernel (Francisco and Resurreccion 2008). The major flavonol in seed is quercetin (Singleton et al 2002;Kuhnle et al 2008;Wang et al 2008). Isoflavones in peanuts and other legumes include daidzein, genistein, glycitein and formononetin (Francisco and Resurreccion 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The biologically active polyphenols like trans-resveratrol (Sobolev and Cole 1999), flavonoids like proanthocyanidins (Gu et al 2004), quercetin (Wang et al 2008), and daidzein & genistein (Francisco and Resurreccion 2008) are present in peanut. The quantities of these biologically active chemicals in peanut seed vary depending on genotypes, growth conditions, maturity periods, size of seeds and testa colors etc.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on peanut flavonoids, however, have so far focused on the flavonoid types found in seeds (Wang et al 2008), the variation in the range of flavonoid contents, and the relationship between flavonoid content and seed-coat color (Wang et al 2013, Chukwumah et al 2009, Yoav et al 2012). High quality is important for cultivar breeding, at the same time yield and resistant traits are also major factors in breeding research.…”
Section: Hou Et Almentioning
confidence: 99%
“…Peanut seeds contain abundant flavonoid secondary metabolites (Wang et al 2008), are a popular food source, have preventive effects on metabolic diseases such as diabetes and hypertension, and can also be used in food production as an antioxidant of edible oil (Chukwumah et al 2009, Lopes et al 2011. Therefore, the flavonoid content of peanut seeds has already aroused the attention of many scholars.…”
Section: Introductionmentioning
confidence: 99%